What lies beneath: Foreign exchange rate exposure, hedging and cash flows - Bartram, Söhnke M. (Journal of Banking & Finance, 2008)
This paper presents results from an in-depth analysis of the foreign exchange rate exposure of a large nonfinancial firm based on proprietary internal data including cash flows, derivatives and foreign currency debt, as well as external capital market data. While the operations of the multinational firm have significant exposure to foreign exchange rate risk due to foreign currency-based activities and international competition, corporate hedging mitigates this gross exposure. The analysis illustrates that the insignificance of foreign exchange rate exposures of comprehensive performance measures such as total cash flow can be explained by hedging at the firm level. Thus, the residual net exposure is economically and statistically small, even if the operating cash flows of the firm are significantly exposed to exchange rate risk. The results of the paper suggest that managers of nonfinancial firms with operations exposed to foreign exchange rate risk take savvy actions to reduce exposure to a level too low to allow its detection empirically.